Goto? Shinpei, statesman of vision research, public health, and development - Kitaoka, Shin'ichi 1948-; Arthy, Iain (2021)
"The Meiji era (1868-1912) produced numerous geniuses in Japan and one who certainly earns his name on the list is Goto? Shinpei. Goto?, who was a prominent figure in Japan's political scene, showed exceptional talent in various fields. Starting off his career as a physician, he became a leading figure in public health and successfully organized a massive quarantine in 1895 for returning soldiers of the First Sino-Japanese War. Later he was appointed as civilian governor of Taiwan and following this he became the first president of the South Manchuria Railway, showing ingenuity in colonial management which was remarkably different from that of Western countries. He built the basis of the Japanese railway system as director-general of the Railway Agency and as home minister presented a grand vision for urban planning immediately after the Great Kanto? Earthquake of 1923."
Includes bibliographical references (pages 210-213).
Keywords: Goto, Shinpei -- 1857-1929.; Diplomats -- Japan -- Biography; Cabinet officers -- Japan -- Biography; Japan -- Politics and government -- 1868-1912.